Three Phase Trinary Source MLI Using Multicarrier SPWM Strategies - T. Sengolrajan; B. Shanthi; M. Arumugam (Institute of Advanced Engineering and Science, 2015)
This paper presents a comprehensive analysis of various bipolar Multicarrier Pulse Width Modulation (MCPWM) strategies with Sinusoidal reference for three phase Nine level Trinary Source cascaded inverter. A new approach of nine levels is for medium voltage applications. The proposed topology uses reduced number of switching devices and thus reducing losses and low THD in comparison with the conventional topology. The configuration of the circuit is simple and easy to control. Performance factors such as %THD, VRMS where measured and Crest Factor (CF), Distortion Factor (DF), Form Factor (FF) of output voltage were calculated for different modulation indices and the results were compared. VFPWM strategies provides minimum THD and COPWM strategy provides higher fundamental VRMS output voltage. DOI: http://dx.doi.org/10.11591/telkomnika.v13i3.7181